Tanfidz An-Nazhariyah As-Sulukiyah fi Ta’lim Al-Mufradat lit-Thullab Al-Judud bi Ma’had Dar-As-Salam Gontor Al-Haram Al-Awal - Mandrasi Amira Sa'idah; Muhammad Syamsul Arifin; Muhammad Habibirrahman (Rumah Jurnal IAIN Bukittinggi, 2021)
Darussalam Gontor Islamic Institution Campus 1 is an educational institution which prefer on Arabic and English in its curriculum. Actually, Arabic for most of new students has become a new difficult language because only a few of them have learned. Due to solving this circumstance, Arabic teaching learning especially vocabularies must be conducted intensively in the beginning of their studies. Behaviourism theory as one of the psychological theories stated that every human receives types of responses from their environment and always communicate each other by their own languages. Therefore, this theory is a compatible in vocabulary teaching learning that requires stimulus, response, reinforcement and language environment. This study purposed to explore behaviourism in conducting vocabularies teaching learning for new students in Darussalam Gontor Islamic Institution. The study is a field researching as kind of descriptive qualitative study. For data collecting, it used observation, interview and written documents. For analysing data, it used interactive method. The study resulted that behaviourism in conducting vocabularies teaching learning for new students were represented in three aspects: 1) positive stimulus from teacher; 2) positive response from students and 3) positive reinforcement from both teacher-student.معهد دار السلام كونتور الحرم الأول هي مؤسسة تعليمية تفضل اللغتين العربية والإنجليزية في مناهجها. في الواقع ، أصبحت اللغة العربية بالنسبة لمعظم الطلاب الجدد لغة جديدة صعبة لأن القليل منهم فقط قد تعلمها. بسبب حل هذا الظرف ، يجب إجراء تعلم اللغة العربية خاصة المفردات بشكل مكثف في بداية دراستهم. ذكرت نظرية السلوكية كواحدة من النظريات النفسية أن كل إنسان يتلقى أنواعًا من الاستجابات من بيئته ويتواصل دائمًا مع بعضهم البعض بلغاتهم الخاصة. لذلك ، فإن هذه النظرية متوافقة في تعلم المفردات التي تتطلب التحفيز والاستجابة والتعزيز والبيئة اللغوية. تهدف هذه الدراسة إلى استكشاف السلوكيات في إجراء المفردات التي تدرس التعلم للطلاب الجدد في معهد دار السلام كونتور. الدراسة عبارة عن بحث ميداني كنوع من الدراسة الوصفية النوعية. لجمع البيانات ، استخدمت الملاحظة والمقابلة والوثائق المكتوبة. لتحليل البيانات ، استخدمت طريقة تفاعلية. نتج عن الدراسة أن السلوكية في إجراء المفردات التعليمية لتعليم الطلاب الجدد تمثلت في ثلاثة جوانب: 1) التحفيز الإيجابي من المعلم. 2) استجابة إيجابية من الطلاب و 3) التعزيز الإيجابي من كل من المعلم والطالب.